BIOCHEMICAL CHARACTERIZATION AND ANTIMICROBIAL PROPERTIES OF ICE CREAM ENRICHED WITH ANTIOXIDANT ENCAPSULATED PROPOLIS - Mesut Ertan Günes; Saban Keskin; Perihan Erkan Alkan; Merve Keskin; Sevgi Kolayli (Journal of Animal and Plant Sciences, 2024)
Microorganism food poisoning is one of the foodborne illnesses in the world. The interest in natural preservatives has increased since the lack of acceptability in using synthetic preservatives. Propolis, a resinous mixture, is a natural product produced by honey bees to protect their hives against microorganisms. It is considered a natural food supplement and preservative owing to its high antimicrobial and antioxidant activities. However, its resinous nature (not readily soluble in water), ethanol solubility, specific strong smell and taste limits its usage as a natural preservative. Encapsulation of propolis ethanol extract with natural polymers like alginate and pectin may overcome these limitations. Main aim of this study was to test powdered form of propolis as a natural preservative in ice cream as model food. For this purpose propolis, after extraction and characterization, was encapsulated by using pectin and converted into powdered form. Antimicrobial activity of prepared ice cream itself against S. aureus (ATCC 25923), E. coli (ATCC 28712), E. faecalis (ATCC 51299), K. pneumoniae (ATCC 700603) and B. cereus (patient isolate) was tested. Total phenolic content and ferric reducing antioxidant power of propolis were noted as 46.26 ±1.18 mg GAE/mL and as 0.27 ±0.07 µmol FeSO4.7H2O/mL, respectively. The encapsulation efficiency was found 95%. Encapsulation of propolis ethanol extract improved the homogenization of propolis active compounds in ice cream. This resulted in obtaining an ice cream with high antimicrobial and antioxidant activities. In conclusion, the use of encapsulated active compounds of propolis ethanol extract improved the both antimicrobial and antioxidant activity of the ice cream produced in a natural way.
Keywords: antioxidant activity; antimicrobial activity; ionic gelation; ice cream; propolis